Analisis Data Pergerakan Harga Saham Bank BUMN melalui Debt to Equity Ratio (DER), Return On Equity (ROE) dan Earning Per Share (EPS) - Hairul Anam; Aditya Achmad Rakim; Saiful Ghozi; Winarni Winarni (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
The purpose of this study was to determine the effect of Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices. Data were obtained from the Annual Report issued by the Indonesia Stock Exchange with the 2009-2017 period. In this study used saturated sampling techniques and samples in the study are State-Owned Enterprised Banks listed on the Indonesia Stock Exchange for the period 2009-2017. The analysis technique used in this study is multiple linear regression analysis to obtain a comprehensive picture of the relationship between variables one with other variablesBased on the results of testing hypotheses using simultaneous test (F) statistics concluded that Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Per Share (EPS) simultaneously had a significant effect on Stock Prices. Based on partial test (t) it was concluded that Debt to Equity Ratio (DER), partially significant effect on Stock Price, Return On Equity (ROE) partially significant effect on Stock Price and Earning Per Share (EPS) partially significant effect on Stock Price.The purpose of this study was to determine the effect of Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices. Data were obtained from the Annual Report issued by the Indonesia Stock Exchange with the 2009-2017 period. In this study used saturated sampling techniques and samples in the study are State-Owned Enterprised Banks listed on the Indonesia Stock Exchange for the period 2009-2017. The analysis technique used in this study is multiple linear regression analysis to obtain a comprehensive picture of the relationship between variables one with other variablesBased on the results of testing hypotheses using simultaneous test (F) statistics concluded that Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Per Share (EPS) simultaneously had a significant effect on Stock Prices. Based on partial test (t) it was concluded that Debt to Equity Ratio (DER), partially significant effect on Stock Price, Return On Equity (ROE) partially significant effect on Stock Price and Earning Per Share (EPS) partially significant effect on Stock Price.